Cultural Interactions in the Medieval Subcaucasian Region: Historiographical and Art-Historical Perspectives Vol. I The Othering Gaze: Imperialism, Colonialism, and Orientalism in Studies on Medieval Art in the Southern Caucasus (1801-1991) - Adrien, Palladino (Collana: Convivia, 2023)
This collaborative volume explains the nineteenth and twentieth century marginalization of one of the major centers of medieval culture and creativity, the Southern Caucasus, through an in depth histo-riographical approach. Tracing research traditions created within different linguistic spheres (Russian, German, French, Italian, and English) across time, it shows how and to what extent the birth of art historical studies on the region were conditioned by geopolitical stakes and by the social and cul-tural perception of the modern regions. From the creation of the Russian Caucasus Viceroyalty in 1801 until the end of the Cold War in 1991, the volume dissects how the region's medieval art was rediscov-ered, studied, and presented. In doing so, it decon-structs some of the most deeply rooted stereotypes of the discipline while at the same actively partici-pating in demarginalizing this region and affording it its rightful place in world art history.